2015
DOI: 10.2147/copd.s89763
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is associated with the severity of COPD: a systematic review and meta-analysis

Abstract: PurposeTo explore the association between host serum 25-hydroxyvitamin D (25(OH)D) and the susceptibility and severity of COPD.MethodsPrevious studies on the association between host 25(OH)D and the susceptibility and severity of COPD were collected on the basis of a systematic literature search of PubMed and Web of Science up to June 2015. Continuous variable data were presented as standard mean difference (SMD) or weighted mean difference with 95% confidence interval (CI). The dichotomous variable data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…Zhang et al15 just included two studies, and no statistical significance was found in the analysis. Zhu et al16 conducted a meta-analysis of 18 studies. The analysis showed that the serum levels of 25(OH) D were lower in COPD patients and vitamin D deficiency was associated with COPD severity rather than COPD risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al15 just included two studies, and no statistical significance was found in the analysis. Zhu et al16 conducted a meta-analysis of 18 studies. The analysis showed that the serum levels of 25(OH) D were lower in COPD patients and vitamin D deficiency was associated with COPD severity rather than COPD risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, the conclusion was not definite. Two meta-analyses on the roles of vitamin D in COPD have been conducted 15,16. However, the studies did not include enough articles, did not extract correct data, pooled the levels of vitamin D from serum and plasma, included participants with vitamin D supplement, or did not analyze the sources of high heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 92 93 94 95 ] Moreover, 25(OH)D levels were lower in advanced stages,[ 8 92 93 94 95 ] suggesting a link between COPD severity and vitamin D deficiency. [ 96 ] The exact reason for such a link is unknown, vitamin D deficiency may be caused by decreased sunlight exposure, poor diet and smoking itself [ 97 ] in COPD subjects. It has also been postulated that the vitamin D status may affect COPD development and exacerbations.…”
Section: Disease-specific Risk Factors For Osteoporosis In Copdmentioning
confidence: 99%
“…Recent meta-analyses have concluded that vitamin D deficiency is directly associated with COPD disease severity and vitamin D supplementation may prevent exacerbations 1012. It is purported that this association is mediated through the immunomodulatory effects of vitamin D13 by shifting the inflammatory balance from a pro-inflammatory T-helper cell 1 profile toward a more anti-inflammatory T-helper cell 2 profile 14,15.…”
Section: Introductionmentioning
confidence: 99%